RT Glomangioma on Right Forearm - A Rare Case Report - Santosh L. Munde; Hemlata T. Kamra; Kulwant Singh; Swaran Kaur; Parveen Kundu (Journal of Krishna Institute of Medical Sciences University, 2016)
Glomangioma is very rare lesion in extradigital location. They are usually associated with multiple and familial lesion. Glomangioma as with glomus tumour also presents with hypersensitivity to cold, severe pain and pinpoint tenderness to blunt palpation. Glomus tumours have not been observed in individuals who are less than one year of age (glomus bodies form after that age) or in elderly persons (glomus bodies undergo atrophy and degeneration in elderly persons). Diagnosis is conrmed by histopathological diagnosis but should be differentiated from glomangiosarcoma which shows nuclear atypia and mitotic activity. We here present a case of glomangioma in a 28 years male on right forearm.